'Do the resilient things.' Residents' perspectives on responsibilities for flood risk adaptation in England. Issue 3 (11th June 2021) - Snel, Karin A. W.; Priest, Sally J.; Hartmann, Thomas; Witte, Patrick A.; Geertman, Stan C. M.
Abstract: Residents should take adaptive action to reduce flood risk—this claim increasingly resonates in the academic debate on flood risk management (FRM). Hence, it must be assumed that a change in the division of responsibilities between actors involved is an imperative, that is, beyond the public authorities, residents should become more responsible for their own flood resilience. However, residents' perspectives on their own and other's responsibility for adaptive action has not yet been explored extensively. In this contribution, we distinguish between four notions of responsibility in analysing the perspectives of residents regarding flood risk adaptation measures undertaken by public authorities, insurance companies and residents themselves. A qualitative study in England shows how residents perceive responsibilities for flood risk adaptation across the various notions and actors, including themselves. We found that residents have clear expectations and perceptions on how they think responsibility is divided among stakeholders and how they would like it to be. Additionally, the discourse on responsibility division in FRM raises questions and causes mismatches between the formal legal parameters and residents' perceptions. With the insights into residents' perceptions, opportunities arise to better inform and encourage them to take flood risk adaptation measures and thereby improve flood resilience.